Historia y Arte en la plástica de Cuba y Puerto Rico: puentes entre dos tiempos, entre dos aguas - Arango Milián, Haydée (2017)
Pedro Álvarez (Cuba) and Rafael Trelles (Puerto Rico) are two important exponents of contemporary art in the Hispanic-speaking Caribbean who found in two artistic milestones of the nineteenth century a way to question the formulas established by History and Art. Both, from the reappropriation of the work of Víctor Patricio Landaluze and Francisco Oller, respectively, reflect on the complex circumstances of their islands. Through the study of the past, both are committed to the sense of their homeland history, to the (re)updating of their artistic tradition or to the functions of the intellectual in the configuration of their national contexts. Fragmentation and collage are effective constructive methods used by both artists to decontextualize the multiple cultural signs of their starting referents and to readjust their multiple meanings in the new work and in the new context. Nevertheless, in spite of the similarities, differences of intention are also noticed, according to the respective national realities: while the Puerto Rican has the clear purpose of paying homage to Oller, the Cuban intends to claim the figure of Landaluze, in whom he finds inspiration for depicting the present.